Finite‐time convergence of group flocking for multi‐agent systems with mismatched/matched disturbances. Issue 6 (4th November 2020) - Yang, Yi‐ze; Yang, Hong‐yong; Li, Yuling
Abstract : In this study, the problem of grouping motion for a second‐order multi‐agent network with both matched disturbances and mismatched disturbances is investigated, and finite‐time convergent algorithm of the dynamic system is proposed. By designing the disturbance observers to eliminate disturbances in the multi‐agent systems, a compound communication protocol with active disturbance compensation is presented by means of the sliding‐mode control. By applying finite‐time stable theory and input‐to‐state stable theory, the finite‐time group convergence of multi‐agent systems with multiple disturbances is analysed, and group flocking can be achieved asymptotically with the cooperative controller. The numerical simulations demonstrate the validity of the results.